Sealing composition, method for producing same, and sealing sheet

JP7643359B2Active Publication Date: 2025-03-11AJINOMOTO CO INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022007835
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-01-21
Publication Date
2025-03-11
Estimated Expiration
2042-01-21

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、水蒸気浸入バリア性および透明性を両立した封止層を形成し得、さらに酸化カルシウムの分散性(保存安定性)に優れた封止用組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643359000001
    Figure 0007643359000001
  • Figure 0007643359000002
    Figure 0007643359000002
  • Figure 0007643359000003
    Figure 0007643359000003
Patent Text Reader

Abstract

To provide a sealing composition that is capable of forming a sealing layer having both of a barrier against steam intrusion and transparency and also has superior dispersibility (storage stability) of calcium oxide.SOLUTION: A sealing composition includes following components (A)-(D): (A) an olefinic polymer having an acid anhydride group and / or a carboxy group with a number average molecular weight of less than 10,000, (B) a polymer with a number average molecular weight of 10,000 or more, (C) calcium oxide with a median size of 300 nm or less, and (D) a nonionic surfactant and / or an anionic surfactant.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealing composition useful for sealing electronic devices and the like. [Background technology]

[0002] In order to protect electronic devices such as organic EL (Electroluminescence) devices and solar cells from moisture, electronic devices are sealed using a sealing layer formed from a sealing composition or a sealing sheet. For example, Patent Document 1 discloses a sealing resin composition containing (A) a polyolefin resin and (B) a metal hydroxide selected from the group consisting of hydrotalcite and semi-calcined hydrotalcite, as well as a sealing sheet formed therefrom, which have good moisture resistance and transparency. However, hydrotalcite reversibly absorbs and releases moisture. Therefore, in a sealing composition using hydrotalcite, moisture absorbed by the hydrotalcite during the manufacturing process or distribution process is released in the sealing layer of an electronic device formed using the composition, which may cause deterioration of the electronic device. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2017 / 057708 Summary of the Invention [Problem to be solved by the invention]

[0004] Calcium oxide is known as a hygroscopic filler. Although a sealing layer formed from a sealing composition obtained by using calcium oxide has excellent properties of suppressing the intrusion of water vapor (sometimes referred to as "water vapor intrusion barrier property" in this specification), when calcium oxide is contained as a hygroscopic filler in a sealing composition containing an olefin-based polymer, the transparency of the sealing layer formed from the composition is usually lost. In order to suppress the decrease in transparency, it is considered to use fine calcium oxide, but since fine calcium oxide has poor dispersibility, it has been difficult to produce a composition having excellent transparency in which fine calcium oxide is well dispersed in an olefin-based polymer. Therefore, it has been difficult to achieve both water vapor intrusion barrier property and transparency in a sealing layer formed from a sealing composition containing an olefin-based polymer.

[0005] Therefore, an object of the present invention is to provide a sealing composition which is capable of forming a sealing layer having both water vapor barrier properties and transparency, and further has excellent dispersibility of calcium oxide (storage stability). [Means for solving the problem]

[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that, in a sealing composition containing the following components (A) to (C), by further containing component (D): a nonionic surfactant and / or an anionic surfactant, a sealing layer that exhibits both water vapor barrier properties and transparency can be formed, and the sealing composition further exhibits excellent dispersibility of calcium oxide (storage stability), and have thus completed the present invention.

[0007] That is, the present invention has the following features. [1] An encapsulating composition comprising the following components (A) to (D): (A) an olefin polymer having an acid anhydride group and / or a carboxy group and a number average molecular weight of less than 10,000; (B) a polymer having a number average molecular weight of 10,000 or more; (C) calcium oxide having a median diameter of 300 nm or less, and (D) Nonionic surfactants and / or anionic surfactants. [2] The sealing composition according to [1], wherein the component (D) is a nonionic surfactant. [3] The sealing composition according to [2], wherein the nonionic surfactant is a polyoxyalkylene alkyl ether or a polyoxyalkylene aryl ether. [4] The sealing composition according to [2], wherein the nonionic surfactant is a polyoxyalkylene aryl ether. [5] The nonionic surfactant has the following structure:

[0008] [ka]

[0009] (wherein n is an integer of 1 to 10, R1 and R2 each independently represent a hydrogen atom or a methyl group, and Ar represents an aromatic group which may have a substituent). [6] The encapsulating composition according to any one of [1] to [5], wherein the polymer (B) having a number average molecular weight of 10,000 or more is an olefin-based polymer having a number average molecular weight of 10,000 or more. [7] The encapsulating composition according to [6], wherein the polymer (B) having a number average molecular weight of 10,000 or more is at least one selected from the group consisting of an olefin polymer having an acid anhydride group and / or a carboxy group and having a number average molecular weight of 10,000 or more, and an olefin polymer having an epoxy group and having a number average molecular weight of 10,000 or more. [8] The encapsulating composition according to any one of [1] to [7], further comprising (E) a liquid olefin polymer (excluding the components (A) and (B)). [9] The sealing composition according to any one of [1] to [8], further comprising (F) a tackifier.

[10] The sealing composition according to any one of [1] to [9], wherein the content of the component (C) is 10 to 70 mass % relative to 100 mass % of the nonvolatile content of the sealing composition.

[11] The sealing composition according to any one of [1] to

[10] , wherein the content of the component (D) is 5 to 25 mass % relative to 100 mass % of the nonvolatile content of the sealing composition.

[12] A sealing sheet having a laminated structure including a sealing layer formed from the sealing composition according to any one of [1] to

[11] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a sealing composition capable of forming a sealing layer that has both water vapor barrier properties and transparency, and further has excellent dispersibility of calcium oxide (storage stability). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described with reference to preferred embodiments thereof. [Sealing composition] The sealing composition of the present invention contains the following components (A) to (D) as essential components: (A) an olefin polymer having an acid anhydride group and / or a carboxy group and a number average molecular weight of less than 10,000; (B) a polymer having a number average molecular weight of 10,000 or more; (C) calcium oxide having a median diameter of 300 nm or less, and (D) Nonionic surfactants and / or anionic surfactants.

[0012] By using calcium oxide, which has a higher hygroscopicity than the hydrotalcite described in Patent Document 1, as the hygroscopic filler, it is possible to form a sealing layer that has an excellent barrier property against water vapor penetration.

[0013] When calcium oxide is used, the transparency of the resulting sealing layer decreases. In this regard, in the present invention, calcium oxide (component (C)) having a median diameter of 300 nm or less is used, thereby making it possible to suppress the decrease in transparency.

[0014] It is difficult to disperse the fine (C) component well in the sealing composition. However, in the present invention, the use of an olefin-based polymer ((A)) having an acid anhydride group and / or a carboxyl group with a number average molecular weight of less than 10,000 improves the dispersibility of the fine (C) component in the sealing composition. In this respect, it is presumed that the (A) component functions as a dispersant for the fine (C) component. However, the present invention is not limited to such a presumption.

[0015] However, the dispersibility of the component (C) is not necessarily sufficient, and aggregation of calcium oxide and gelation of the composition varnish may occur during preparation (mixing) of the composition varnish for producing the sealing sheet or during storage of the varnish. Such aggregation and gelation can be prevented by further adding a nonionic surfactant and / or anionic surfactant (component (D)) to the sealing composition.

[0016] In this specification, the term "olefin polymer" refers to a polymer in which a structural unit derived from an olefin (hereinafter sometimes abbreviated as "olefin unit") is the main structural unit (i.e., the amount of olefin unit is the largest among all structural units). In the following, the olefin unit "structural unit derived from butene" etc. may be abbreviated as "butene unit" etc.

[0017] The olefin polymer may be an olefin resin (e.g., a propylene-butene copolymer) or an olefin rubber (e.g., a butyl rubber, i.e., an isobutene-isoprene copolymer). In this specification, the term "olefin resin" refers to an olefin polymer that cannot form a rubber elastomer by crosslinking, and the term "olefin rubber" refers to an olefin polymer that can form a rubber elastomer by crosslinking.

[0018] The olefin is preferably a monoolefin having one olefinic carbon-carbon double bond and / or a diolefin having two olefinic carbon-carbon double bonds. Examples of the monoolefin include α-olefins such as ethylene, propylene, 1-butene, isobutene (isobutylene), 1-pentene, 1-hexene, 1-heptene, and 1-octene. Examples of the diolefin include 1,3-butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethylbutadiene.

[0019] The olefin-based polymer may be a homopolymer or a copolymer. The copolymer may be a random copolymer or a block copolymer. The olefin-based polymer may be a copolymer of an olefin and a monomer other than an olefin. Examples of the olefin-based copolymer include an ethylene-non-conjugated diene copolymer, an ethylene-propylene copolymer, an ethylene-propylene-non-conjugated diene copolymer, an ethylene-butene copolymer, an ethylene-propylene-butene copolymer, a propylene-butene copolymer, a propylene-butene copolymer, a propylene-butene-non-conjugated diene copolymer, an isobutene-isoprene copolymer, a styrene-isobutene copolymer, and a styrene-isobutene-styrene copolymer.

[0020] Each component will be described in detail below. Note that, unless otherwise specified in this specification, each component may be used alone or in combination of two or more kinds.

[0021] <Component (A)> Component (A) is an olefin polymer having an acid anhydride group (i.e., a carbonyloxycarbonyl group (-CO-O-CO-)) and / or a carboxy group with a number average molecular weight of less than 10,000. By blending component (A), calcium oxide (component (C)) can be well dispersed in the sealing composition. In addition, the acid anhydride group / carboxy group reacts with an epoxy group or coordinates with calcium oxide to form a crosslinked structure, thereby exhibiting water vapor penetration barrier properties. Component (A) is preferably an olefin polymer having an acid anhydride group with a number average molecular weight of less than 10,000.

[0022] When an olefin polymer having an acid anhydride group and a number average molecular weight of less than 10,000 is used as component (A), the concentration of the acid anhydride group in the polymer is preferably 0.05 to 10 mmol / g, more preferably 0.10 to 5 mmol / g. The concentration of the acid anhydride group is obtained from the acid value, which is defined as the number of milligrams of potassium hydroxide required to neutralize the acid present in 1 g of the polymer, according to the description of JIS K 2501.

[0023] When an olefin polymer having a number average molecular weight of less than 10,000 and containing carboxy groups is used as component (A), the concentration of the carboxy groups in the polymer is preferably 0.05 to 20 mmol / g, more preferably 0.10 to 10 mmol / g. The concentration of the carboxy groups is determined from the acid value, which is defined as the number of milligrams of potassium hydroxide required to neutralize the acid present in 1 g of the polymer, according to JIS K 2501.

[0024] When an olefin polymer having an acid anhydride group and a carboxy group and a number average molecular weight of less than 10,000 is used as the component (A), the sum of the concentration of the acid anhydride group and the concentration of the carboxy group in the polymer is preferably 0.05 to 20 mmol / g, more preferably 0.10 to 10 mmol / g.

[0025] The number average molecular weight of the (A) component is less than 10,000, and is preferably 100 to 10,000, more preferably 250 to 9,000, and even more preferably 500 to 8,000, from the viewpoint of improving the coating property of the varnish of the sealing composition and the sealing performance and mechanical strength of the sealing layer formed. The number average molecular weight of each component is measured by gel permeation chromatography (GPC) method (polystyrene equivalent). Specifically, the number average molecular weight by the GPC method is measured at a column temperature of 40°C using Shimadzu Corporation's "LC-9A / RID-6A" as a measuring device, Showa Denko Corporation's "Shodex K-800P / K-804L / K-804L" as a column, toluene or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.

[0026] The component (A) can be produced, for example, by (i) graft-modifying an olefin polymer with an unsaturated compound having an acid anhydride group and / or a carboxy group (e.g., maleic anhydride) under radical reaction conditions, or by (ii) copolymerizing an unsaturated compound having an acid anhydride group and / or a carboxy group with an α-olefin.

[0027] As the component (A), for example, a polymer available from Toho Chemical Industry Co., Ltd., Seiko PMC Co., Ltd., etc., can be used. Examples of such polymers include "HV-300M" (maleic anhydride modified liquid polybutene) manufactured by Toho Chemical Industry Co., Ltd., "HV-100M" (maleic anhydride modified liquid polybutene) manufactured by Toho Chemical Industry Co., Ltd., "ER688" (maleic anhydride modified liquid polybutene) manufactured by Seiko PMC Co., Ltd., "LUCANT A-5515" (acid-modified ethylene-α-olefin copolymer) manufactured by Mitsui Chemicals, Inc., and "LUCANT A-5260" (acid-modified ethylene-α-olefin copolymer) manufactured by Mitsui Chemicals, Inc. Examples of suitable polymers include "Lucant A-5320H" (acid-modified ethylene-α-olefin copolymer) manufactured by Mitsui Chemicals, "T-YP430" (maleic anhydride-modified ethylene-methyl methacrylate copolymer) manufactured by Seiko PMC, "T-YP956" (maleic anhydride-modified ethylene-propylene-butene random copolymer) manufactured by Seiko PMC, and "Diacarna 30M" (copolymer of maleic anhydride and α-olefin) manufactured by Mitsubishi Chemical.

[0028] In one embodiment of the present invention, the component (A) has a number average molecular weight of less than 10,000. (i) preferably at least one selected from the group consisting of polybutene having an acid anhydride group and / or a carboxy group, isobutene-isoprene copolymer having an acid anhydride group and / or a carboxy group (i.e., butyl rubber), propylene-butene copolymer having an acid anhydride group and / or a carboxy group, ethylene-methyl methacrylate copolymer having an acid anhydride group and / or a carboxy group, and ethylene-propylene-butene copolymer having an acid anhydride group and / or a carboxy group, (ii) More preferably, it is at least one selected from the group consisting of polybutene having an acid anhydride group and / or a carboxy group, an isobutene-isoprene copolymer having an acid anhydride group and / or a carboxy group, and a propylene-butene copolymer having an acid anhydride group and / or a carboxy group, (iii) More preferably, it is at least one selected from the group consisting of polybutene having an acid anhydride group, isobutene-isoprene copolymer having an acid anhydride group, and propylene-butene copolymer having an acid anhydride group, (iv) Polybutene having an acid anhydride group is particularly preferred.

[0029] From the viewpoint of dispersibility of fine calcium oxide (component (C)) in the sealing composition, the content of component (A) is preferably 3 to 50 mass %, more preferably 5 to 45 mass %, and even more preferably 10 to 40 mass %, relative to 100 mass % of the nonvolatile content of the sealing composition.

[0030] <(B) component> The component (B) is a polymer having a number average molecular weight of 10,000 or more. By blending the component (B), a sealing layer that is difficult to deform and can maintain its shape can be obtained. If the component (B) is not blended, film formation becomes difficult. The polymer of the component (B) is not particularly limited as long as it has a number average molecular weight of 10,000 or more, but an olefin-based polymer is preferable from the viewpoint of compatibility. In addition, from the viewpoint of dispersibility of calcium oxide (component (C)) in the sealing composition and the water vapor penetration barrier property of the resulting sealing layer, at least one selected from an olefin-based polymer having an acid anhydride group and / or a carboxy group having a number average molecular weight of 10,000 or more (hereinafter also referred to as "component (B1)") that can form a crosslinked structure by reaction between an epoxy group and an acid anhydride group / carboxy group, or can form a crosslinked structure by coordination of an acid anhydride group / carboxy group to calcium oxide, and an olefin-based polymer having an epoxy group and a number average molecular weight of 10,000 or more (hereinafter also referred to as "component (B2)") is preferable.

[0031] ((B1) component) The olefin polymer having an acid anhydride group and / or a carboxy group as the component (B1) polymer is as explained above for the component (A) except that the number average molecular weight is 10,000 or more.

[0032] As the component (B1), for example, a polymer available from Seiko PMC Co., Ltd. can be used. Examples of such polymers include "ER645" (maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., "ER661" (maleic anhydride-butyl methacrylate random copolymer modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "ER641" (maleic anhydride modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "ER669" (maleic anhydride-2-ethylhexyl acrylate random copolymer modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "ER674" (maleic anhydride-lauryl methacrylate random copolymer modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "T-YP279" (maleic anhydride modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., and "T-YP212" (maleic anhydride modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., and the like.

[0033] ((B2) component) The epoxy group concentration in the component (B2) is preferably 0.05 to 10 mmol / g, and more preferably 0.10 to 5 mmol / g. The epoxy group concentration is determined from the epoxy equivalent obtained based on JIS K 7236-1995.

[0034] The component (B2) can be obtained, for example, by (i) graft-modifying an olefin polymer with an unsaturated compound having an epoxy group (e.g., glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, allyl glycidyl ether) under radical reaction conditions, or by (ii) copolymerizing an unsaturated compound having an epoxy group with an α-olefin.

[0035] As the component (B2), for example, a polymer available from Sumitomo Chemical Co., Ltd., Seiko PMC Co., Ltd., etc. can be used. Examples of such a polymer include "BONDFAST BF-7M" (ethylene-glycidyl methacrylate copolymer) manufactured by Sumitomo Chemical Co., Ltd., "BONDFAST Examples of such copolymers include "BF-2B" (ethylene-glycidyl methacrylate-vinyl acetate copolymer), "BF-7L" (ethylene-glycidyl methacrylate-methyl acrylate copolymer) manufactured by Sumitomo Chemical Co., Ltd., "ER829" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., "ER850" (glycidyl methacrylate modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "ER853" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., "ER866" (glycidyl methacrylate modified butyl rubber) manufactured by Seiko PMC Co., Ltd., "T-YP276" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd., and "T-YP313" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Seiko PMC Co., Ltd.

[0036] The (B2) component has a number average molecular weight of 10,000 or more. (i) preferably at least one selected from the group consisting of ethylene-glycidyl methacrylate copolymer, ethylene-glycidyl methacrylate-vinyl acetate copolymer, ethylene-glycidyl methacrylate-methyl acrylate copolymer, propylene-butene copolymer having an epoxy group, isobutene-isoprene copolymer having an epoxy group (i.e., butyl rubber), and ethylene-methyl methacrylate copolymer having an epoxy group; (ii) More preferably, it is at least one selected from the group consisting of a propylene-butene copolymer having an epoxy group, an isobutene-isoprene copolymer having an epoxy group, and an ethylene-methyl methacrylate copolymer having an epoxy group; (iii) More preferably, it is a propylene-butene copolymer having an epoxy group, and / or an isobutene-isoprene copolymer having an epoxy group, (iv) Particularly preferred are propylene-butene copolymers having epoxy groups, and isobutene-isoprene copolymers having epoxy groups.

[0037] When a propylene-butene copolymer having an epoxy group and a number average molecular weight of 10,000 or more is used as the component (B2), the amount of butene units in the copolymer is preferably 1 to 50 mass%, more preferably 2 to 45 mass%, and even more preferably 3 to 40 mass% based on the total of propylene units and butene units. The amount of butene units is based on the propylene units and butene units excluding modified portions (for example, portions derived from glycidyl (meth)acrylate for introducing epoxy groups).

[0038] When an isobutene-isoprene copolymer having an epoxy group with a number average molecular weight of 10,000 or more (i.e., butyl rubber) is used as the component (B2), the amount of isoprene units in the copolymer is preferably 0.1 to 20 mass%, more preferably 0.3 to 15 mass%, and even more preferably 0.5 to 10 mass% based on the total of isobutene units and isoprene units, from the viewpoint of yellowing resistance of the sealing layer, etc. The amount of isoprene units is based on the isobutene units and isoprene units excluding modified portions (for example, portions derived from glycidyl (meth)acrylate for introducing epoxy groups).

[0039] When the (B1) component and the (B2) component are used in combination as the (B) component, it is preferable that the amount of the (B2) component and the amount of the (B1) component are determined by the ratio of the functional groups they have. Although it varies depending on the crosslinking conditions (temperature, time), etc., the "amount (mol) of epoxy groups in the (B2) component": "the total amount (mol) of acid anhydride groups and the amount (mol) of carboxy groups in the (B1) component" is preferably 100:30 to 100:1500, more preferably 100:50 to 100:1250, even more preferably 100:60 to 100:1000, and particularly preferably 100:70 to 100:900. For example, when the (B1) component has only acid anhydride groups, the "total amount (mol) of acid anhydride groups and the amount (mol) of carboxy groups" means the "amount (mol) of acid anhydride groups".

[0040] As the component (B), an olefin-based polymer other than the components (B1) and (B2), i.e., a non-liquid olefin-based polymer having a number average molecular weight of 10,000 or more and having no acid anhydride group, carboxy group, or epoxy group (hereinafter also referred to as "component (B3)") may be used.

[0041] In the present invention, the term "non-liquid" in the "non-liquid olefin polymer" means that the viscosity at 25°C is more than 5,000 Pa·s.

[0042] As the component (B3), for example, a polymer available from JSR Corp., etc., can be used. Examples of such polymers include "BUTYL065" manufactured by JSR Corp., "BUTYL268" manufactured by JSR Corp., "BUTYL365" manufactured by JSR Corp. (all butyl rubbers), "X1102" manufactured by Sumitomo Chemical Co., Ltd., "X1104" manufactured by Sumitomo Chemical Co., Ltd. (all propylene-butene copolymers), "ENGAGE" manufactured by DOW Corp. (polyolefin elastomer), and "RT2315" manufactured by REXtac Corp. (propylene-ethylene copolymer).

[0043] The component (B3) has a number average molecular weight of 10,000 or more. (i) preferably a propylene-butene copolymer and / or an isobutene-isoprene copolymer (i.e., butyl rubber); (ii) More preferably, it is an isobutene-isoprene copolymer.

[0044] When a propylene-butene copolymer having a number average molecular weight of 10,000 or more is used as the component (B3), the amount of butene units in the copolymer is preferably 1 to 50 mass%, more preferably 2 to 45 mass%, and even more preferably 3 to 40 mass%, based on the total of propylene units and butene units.

[0045] When an isobutene-isoprene copolymer (i.e., butyl rubber) having a number average molecular weight of 10,000 or more is used as the component (B3), from the viewpoint of the yellowing resistance of the sealing layer, the amount of isoprene units in the copolymer is preferably 0.1 to 20 mass%, more preferably 0.3 to 15 mass%, and even more preferably 0.5 to 10 mass%, per total of isobutene units and isoprene units.

[0046] The number average molecular weight of component (B) is 10,000 or more, and from the viewpoints of achieving good coatability of the varnish of the sealing composition and improving the sealing performance and mechanical strength of the formed sealing layer, it is preferably 10,000 to 500,000, and more preferably 15,000 to 400,000.

[0047] From the viewpoint of forming a sealing layer that is resistant to deformation and can retain its shape, the content of the (B) component is preferably 0.1 to 25 mass %, more preferably 1 to 20 mass %, and even more preferably 3 to 15 mass %, relative to 100 mass % of the nonvolatile content of the sealing composition.

[0048] <(C) component> Component (C) is calcium oxide with a median diameter of 300 nm or less. By blending component (C) as a hygroscopic filler, it is possible to impart water vapor barrier properties to the sealing layer formed. In addition, by making the median diameter 300 nm or less, it is possible to form a sealing layer with high transparency.

[0049] The median diameter of the component (C) is 300 nm or less, preferably 250 nm or less from the viewpoint of the transparency of the encapsulating layer to be formed, and preferably 1 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more from the viewpoint of the dispersibility of the component (C) in the encapsulating composition. In one embodiment of the present invention, the median diameter of the component (C) is preferably 1 to 300 nm, more preferably 5 to 250 nm, and even more preferably 10 to 200 nm. The median diameter of the component (C) is the median diameter in a volume-based particle size distribution (particle size distribution) created based on the particle size of the component (C) measured by dynamic light scattering (JIS Z 8828). The dynamic light scattering method is a method of calculating particle size and particle size distribution by analyzing fluctuations corresponding to the speed of Brownian motion from scattered light observed when a laser beam is irradiated to particles in a dispersion medium, using a photon correlation method. Specifically, the median diameter can be measured and calculated as described in the examples.

[0050] As the component (C), calcium oxide having a median diameter of more than 300 nm may be ground and used, or a commercially available calcium oxide having a median diameter of 300 nm or less may be used. Examples of commercially available calcium oxide having a median diameter of more than 300 nm include "QC-X" manufactured by Inoue Sekikogyo Co., Ltd., "WAC series" manufactured by Sankyo Flour Milling Co., Ltd., and "HAL-G", "HAL-J", "HAL-F", "HAL-O", and "HAL-P" manufactured by Yoshizawa Sekikogyo Co., Ltd. Examples of commercially available calcium oxide having a median diameter of 300 nm or less include "CaO Nano Powder" manufactured by Filgen Co., Ltd.

[0051] The content of the component (C) is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the nonvolatile content of the sealing composition, from the viewpoint of the water vapor barrier property of the sealing layer, and is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on 100% by mass of the nonvolatile content of the sealing composition. In one embodiment of the present invention, the content of the component (C) is preferably 5 to 80% by mass, more preferably 10 to 70% by mass, and even more preferably 15 to 60% by mass, based on 100% by mass of the nonvolatile content of the sealing composition.

[0052] <(D) component> The component (D) is a nonionic surfactant and / or anionic surfactant. By adding the component (D), the dispersibility of the component (C) in the sealing composition and the varnish life of the sealing composition can be improved. The component (D) is not particularly limited as long as it is a nonionic surfactant and / or anionic surfactant, and various types can be used. The nonionic surfactant and / or anionic surfactant may be used alone or in combination of two or more types. A nonionic surfactant and an anionic surfactant may also be used in combination. The component (D) is preferably a nonionic surfactant.

[0053] Examples of nonionic surfactants suitable for the present invention include ether types, ester types, sorbitan ester types, sorbitan ester-ethylene oxide adduct types, diester types, monoglyceride types, monoglyceride-ethylene oxide adduct types, triglyceride-ethylene oxide adduct types, sorbitol ester-ethylene oxide adduct types, polyglycerin alkyl ester types, polyetheramine types, alkanolamide types, alkanolamide-ethylene oxide adduct types, amine oxide types, polyethylene glycol-polypropylene glycol-block ether types (polyoxyethylene-polyoxypropylene-block copolymer types), ethylenediamine-based types, and phenol types, of which ether types are preferred.

[0054] Representative examples of ether-type nonionic surfactants include: General formula (1):

[0055] [ka]

[0056] A polyoxyalkylene alkyl ether represented by the formula: General formula (2):

[0057] [ka]

[0058] and polyoxyalkylene alkyl phenyl ethers represented by the following formula:

[0059] In formula (1) and formula (2), R 1 represents an alkyl group or an alkenyl group, the number of carbon atoms of which is preferably 6 to 22, more preferably 8 to 18, and particularly preferably 10 to 15. A represents an alkylene group, and X represents a phenylene group. n represents an integer of 1 to 70, preferably an integer of 10 to 30. The oxyalkylene group represented by AO may be composed of one type of oxyalkylene group such as an ethylene oxide group or a propylene oxide group, or may be composed of multiple types of oxyalkylene groups, such as two types of oxyalkylene groups, an ethylene oxide group and a propylene oxide group.

[0060] Specific examples of polyoxyalkylene alkyl ethers include polyoxyethylene hexyl ether, polyoxyethylene heptyl ether, polyoxyethylene octyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene dodecyl ether (also known as polyoxyethylene lauryl ether), polyoxyethylene tetradecyl ether, polyoxyethylene hexadecyl ether (also known as polyoxyethylene cetyl ether), polyoxyethylene octadecyl ether (also known as polyoxyethylene oleyl ether), polyoxyethylene eicosyl ether, polyoxyethylene oleyl ether, coconut oil reduced alcohol ethylene oxide adduct, beef tallow reduced alcohol ethylene oxide adduct, polyoxyethylene-polyoxypropylene-dodecyl ether (also known as polyoxyethylene-polyoxypropylene-lauryl ether), polyoxypropylene dodecyl ether (also known as polyoxypropylene lauryl ether), and the like. Among these, polyoxyethylene dodecyl ether, polyoxypropylene dodecyl ether, polyoxyethylene-polyoxypropylene-dodecyl ether, and the like are preferable.

[0061] Specific examples of polyoxyalkylene alkyl phenyl ethers include polyoxyethylene hexyl phenyl ether, polyoxyethylene heptyl phenyl ether, polyoxyethylene octyl phenyl ether, polyoxyethylene nonyl phenyl ether, polyoxyethylene decyl phenyl ether, polyoxyethylene dodecyl phenyl ether (also known as polyoxyethylene lauryl phenyl ether), polyoxyethylene tetradecyl phenyl ether, polyoxyethylene hexadecyl phenyl ether, polyoxyethylene octadecyl phenyl ether, polyoxyethylene eicosyl phenyl ether, and the like.

[0062] As the nonionic surfactant in the present invention, commercially available products can be used. Examples of ether-type oils include NOF Corp.'s "Nonion K-204" (polyoxyethylene lauryl ether), "Nonion K-220" (polyoxyethylene lauryl ether), "Nonion K-230", "Persoft NK-60", "Persoft NH-90C", "Persoft NK-100", "Persoft NK-100", "Nonion EAD-13" (all polyoxyethylene alkyl ethers), "Nonion P-208", "Nonion P-210", "Nonion P-213" (all polyoxyethylene cetyl ethers), "Nonion E-202", "Nonion E-202S", "Nonion E-205", "Nonion E-205S", "Nonion E-212", "Nonion E-215", "Nonion E-230" (all polyoxyethylene oleyl ethers), "Nonion S-202", "Nonion S-207", "Nonion S-215", "Nonion S-220" (all polyoxyethylene stearyl ether), "Nonion ID-203", "Nonion ID-206", "Nonion ID-209" (all polyoxyethylene isodecyl ether), "Nonion EH-204" (polyoxyethylene 2-ethylhexyl ether), "Nonion EH-208" (polyoxyethylene 2-ethylhexyl ether), "Polyoxydispanol TOC", "Nonion ET-505", "Nonion ET-507", "Nonion ET-510", "Nonion ET-512", "Nonion ET-515", "Nonion ET-518" (all polyoxyethylene-polyoxypropylene-alkyl ether), "Unilube MS-70K" (polyoxypropylene stearyl ether), "Dispanol 16", "Dispanol 16A", "Dispanol LS-100," "Nonion MN-811," "Dispanol WI-106," "Dispanol WI-115," "Dispanol W1-133," and Takemoto Oil Co., Ltd.'s "Paionin D-1004" (polyoxyethylene octyl ether).

[0063] Other examples include "LB-220", "LB-53B", "LB-720", "LB-820", "LB-54C", "LB-83", "LB-93", "LB-103", "LB-1220", and "LB-1520" (all polyoxyalkylene lauryl ethers), "LA-675B", "LA-775", "LA-875", "LA-975", and "LA-1275" (all polyoxyethylene lauryl ethers), "OA-7" (polyoxyethylene oleyl ether), "TN-40", "TN-80", "TN-100", "TO-120", "UA-70N", "UA-90N", "LO-3", and "LO-7" (all primary alcohol ethoxylates), "SO-80", "SO-105", "SO-120", "SO-135", "SO-145", and "SO-160" (all secondary alcohol ethoxylates).

[0064] Examples of the ester type include NOF Corp.'s "Nonion L-2", "Nonion L-4" (all polyoxyethylene monolaurate), "Nonion S-2", "Nonion S-4", "Nonion S-6", "Nonion S-15", "Nonion S-15K", "Nonion S-15.4", "Nonion S-15.4V", "Nonion S-40" (all polyoxyethylene monostearate), "Nonion O-2", "Nonion O-3", "Nonion O-4", "Nonion O-6" (all polyoxyethylene monooleate), and Adeka Corp.'s "OEG-102" (polyoxyethylene monooleate).

[0065] Examples of sorbitan ester types include "Nonion CP-08R" (sorbitan monocaprylate), "Food Additive Nonionic CP-08R" (sorbitan monocaprylate), "Nonion LP-20R" (sorbitan monolaurate), "Nonion LP-20R Food Additive" (sorbitan monolaurate), "Nonion MP-30R" (sorbitan monomyristate), "Nonion PP-40R Pellet" (sorbitan monopalmitate), "Nonion SP-60R Pellet" (sorbitan monostearate), "Nonion OP-80R" (sorbitan monooleate), "Nonion OP-83RAT" (sorbitan sesquioleate), and "Nonion OP-85R" (sorbitan trioleate), and Adeka Corporation's "S-20" (sorbitan lauryl ester), "S-60" (sorbitan stearyl ester), and "S-80" (sorbitan oleyl ester).

[0066] Examples of sorbitan ester-ethylene oxide adducts include NOF Corp.'s "Nonion LT-221" (polyoxyethylene sorbitan monolaurate), "Nonion ST-221" (polyoxyethylene sorbitan monostearate), "Nonion OT-221" (polyoxyethylene sorbitan monooleate), "Willsurf TF-20" (polyoxyethylene sorbitan monolaurate), "Willsurf TF-60" (polyoxyethylene sorbitan monostearate), and "Willsurf TF-80" (polyoxyethylene sorbitan monooleate), as well as ADEKA Corp.'s "T-81" (polyoxyethylene sorbitan monooleate).

[0067] Examples of diester types include NOF Corporation's "Unistar E-275" (ethylene glycol distearate), "Nonion DS-60HN" (polyethylene glycol distearate), "Nonion DO-4" (polyethylene glycol diolate), "Nonion DO-6" (polyethylene glycol diolate), "Unisafe NKL-9520" (polypropylene glycol distearate), and "Unisafe NUL-6589" (polypropylene glycol disuccinate).

[0068] Examples of monoglyceride type include "Monoglyc D" (glyceryl monostearate), "Monoglyc MB" (glyceryl monostearate), and "Monoglyc M-14" (glyceryl monomyristate), all manufactured by NOF Corporation.

[0069] Examples of monoglyceride-ethylene oxide adducts include "Unigly MK-207" (polyoxyethylene cocoate glyceryl), "Unigly MK-230" (polyoxyethylene cocoate glyceryl), and "Unigly MK-278" (polyoxyethylene cocoate glyceryl) manufactured by NOF Corporation, and "NK-3", "NK-4", and "NK-7" (all glyceride-ethylene oxide adducts) manufactured by ADEKA Corporation.

[0070] Examples of triglyceride-ethylene oxide adducts include "Uniox HC-8," "Uniox HC-40," and "Uniox HC-60" (all polyoxyethylene hydrogenated castor oils) manufactured by NOF Corporation.

[0071] Examples of sorbitol ester-ethylene oxide adducts include "UNIOX ST-30E", "UNIOX ST-40E", and "UNIOX ST-60E" (all polyoxyethylene tetraoleate) manufactured by NOF Corporation.

[0072] Examples of polyglycerol alkyl esters include "Unigly GO-102R" (polyglycerol oleate), "Unigly GO-106" (polyglycerol oleate), "Unigly GL-106" (polyglycerol laurate), and "Unigly GS-106" (polyglycerol stearate), all manufactured by NOF Corporation.

[0073] Examples of polyetheramine types include "Nymeen L-201" (N-hydroxyethyl laurylamine), "Nymeen L-202", "Nymeen L-207" (all polyoxyethylene laurylamine), "Nymeen L-703" (polyoxyethylene-polyoxypropylene-laurylamine), "Nymeen F-202", "Nymeen F-215" (all polyoxyethylene alkyl (coconut)amine), "Nymeen S-202", "Nymeen S-204", "Nymeen S-210", "Nymeen S-215", "Nymeen S-220" (all polyoxyethylene stearylamine), "Nymeen O-205" (polyoxyethylene oleylamine), "Nymeen T2-202", "Nymeen T2-210", "Nymeen T2-230" (all polyoxyethylene beef tallow alkylamine), "Nymeen T2-230", "Nymeen DT-203" and "Nymeen DT-208" (polyoxyethylene-alkylpropylene-diamine).

[0074] Examples of alkanolamide types include "Stahome F" (coconut oil fatty acid diethanolamide, 1:2 type), "Stahome T" (beef tallow fatty acid diethanolamide, 1:2 type), "Stahome DL" (lauric acid diethanolamide), "Stahome DF-1", "Stahome DF-2", "Stahome DF-4", "Stahome DFC" (all coconut oil fatty acid diethanolamide), "Stahome DO", "Stahome DOS" (all oleic acid diethanolamide), "Stahome MF Pellet" (coconut oil fatty acid monoethanolamide), "Stahome LIPA" (lauric acid isopropanolamide), etc., manufactured by NOF Corporation, and "CO" (coconut oil fatty acid diethanolamide, 1:2 type) and "COA" (coconut oil fatty acid diethanolamide, 1:1 type), etc., manufactured by ADEKA Corporation.

[0075] Examples of alkanolamide-ethylene oxide adducts include "Nymid MF-203," "Nymid MF-210," and "Nymid MT-215" (all polyoxyethylene fatty acid monoethanolamides) manufactured by NOF Corporation.

[0076] Examples of the amine oxide type include "Unisafe A-LM" (aqueous solution of dimethyl lauryl amine oxide), "Unisafe A-SM" (aqueous solution of dimethyl stearyl amine oxide), "Unisafe A-LE" (aqueous solution of dihydroxyethyl lauryl amine oxide), and "Unisafe WHS-10" (aqueous solution of dihydroxyethyl lauryl amine oxide), all manufactured by NOF Corporation.

[0077] Examples of polyethylene glycol-polypropylene glycol block ether type (polyoxyethylene-polyoxypropylene block copolymer type) include NOF Corp.'s "Pronon #102", "Pronon #104", "Pronon #201", "Pronon #202B", "Pronon #204", "Pronon #208", "Unilube 70DP-600B", and "Unilube 70DP-950B" (all polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers), and ADEKA Corp.'s "L-23". "L-31", "L-44", "L-61", "L-62", "L-64", "L-71", "L-72", "L-101", "L-121", "P-84", "P-85", "P-103", "F-68", "F-88", "F-108" and the like (all polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymers), "25R-1", "25R-2", "17R-2", "17R-3", "17R-4" (all polyoxypropylene-polyoxyethylene-polyoxypropylene block copolymers) and the like.

[0078] Examples of ethylenediamine-based types include "TR-701", "TR-702", and "TR-704" manufactured by Adeka Corporation (all of which are adducts of polyoxyethylene polyoxypropylene block copolymers of ethylenediamine).

[0079] In addition, polyethylene glycols and polypropylene glycols having a hydrophobic group are also suitable nonionic surfactants for the present invention (for example, ether-type nonionic surfactants in which a long-chain alkyl group or a long-chain alkyl-substituted aryl group is bonded to polyethylene glycol as a hydrophobic group). Commercially available polyethylene glycols and polypropylene glycols having a hydrophobic group include, for example, "Pegnol 14-0", "Pegnol 24-0", "Pepol A-0638", "Pepol B-181", "Pepol B-182", "Pepol B-184", "Pepol B-188", and "Pepol BEP-0115" manufactured by Toho Chemical Industry Co., Ltd., and "Nonion A-10R", "Nonion A-13P", "Nonion A-25B", and "Nonion A-25C" manufactured by NOF Corporation. Nonion C-2300, Nonion DIS-400, Nonion DIS-600, Nonion DL-4HN, Nonion DL-40HN, Nonion DO-4HN, Nonion DO-40HN, Nonion DP-1.5HN, Nonion DS-4HN, Nonion DS-40HN, Nonion DS-110HN, Nonion IS-2, Nonion IS-4, Nonion IS-6, Nonion IS-15.4, and the like.

[0080] Furthermore, polymeric compounds having a side chain containing an oxyalkylene group or a polyoxyalkylene group, such as a compound having a segment represented by the following general formula (3), are also suitable nonionic surfactants for the present invention.

[0081] [ka]

[0082] (In the formula, A 1 represents an alkylene group, R 2 represents a hydrogen atom, an alkyl group, or an aryl group, and n represents an integer of 1 to 100. 1The oxyalkylene group represented by -O may be composed of one type of oxyalkylene group such as an ethylene oxide group or a propylene oxide group, or may be composed of multiple types of oxyalkylene groups such as two types of oxyalkylene groups, an ethylene oxide group and a propylene oxide group.

[0083] Other nonionic surfactants that can be used include commercially available polyoxyethylene styryl phenyl ether type products such as Paionin D-6112, Paionin D-6115, Paionin D-6120, Paionin D-6131, Paionin D-6512, Takesurf D-6413, DTD-51, and Paionin D-6320 (all manufactured by Takemoto Oil Co., Ltd.); TS-1500, TS-2000, TS-2600, and SM-174N (all manufactured by Toho Chemical Industry Co., Ltd.); and Emulgen A-60, Emulgen A-90, and Emulgen A-500 (all manufactured by Kao Corporation). Commercially available aryl phenyl ether products include "Paionin D-7240" (polyoxyethylene naphthyl ether) manufactured by Takemoto Oil Co., Ltd., YG-15, Y-PE polyoxyethylene monophenyl ether (manufactured by Yokkaichi Synthetic Co., Ltd.), diethylene glycol monophenyl ether (manufactured by TCI Corporation), dipropylene glycol phenyl ether (manufactured by Dow Corporation), and polyoxyethylene (10) octyl phenyl ether (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0084] In the present invention, the nonionic surfactant is preferably a nonionic surfactant having a polyoxyalkylene skeleton, and the polyoxyalkylene skeleton in the nonionic surfactant having a polyoxyalkylene skeleton is preferably a polyoxyethylene skeleton and / or a polyoxypropylene skeleton.

[0085] In one embodiment of the present invention, the component (D) is preferably a polyoxyalkylene alkyl ether or a polyoxyalkylene aryl ether (preferably, the polyoxyalkylene portion is polyethylene glycol or polypropylene glycol), more preferably a polyoxyalkylene aryl ether (e.g., polyoxyethylene alkyl phenyl ether, polyoxyethylene styryl phenyl ether, etc.), and even more preferably a polyoxyalkylene alkyl ether having the following structure:

[0086] [ka]

[0087] (wherein n is an integer of 1 to 10, R1 and R2 are each independently a hydrogen atom or a methyl group, and Ar is an aromatic group which may have a substituent). It is presumed that these nonionic surfactants exhibit an effect of preventing aggregation of calcium oxide and gelation of the composition varnish due to the presence of a hydrophilic oxyalkylene group in the vicinity of the calcium oxide surface and the presence of an aromatic group in the vicinity of a hydrophobic olefin polymer. However, the present invention is not limited to such a presumption.

[0088] R1 and R2 are preferably both hydrogen atoms.

[0089] Examples of the aromatic group of the "optionally substituted aromatic group" represented by Ar include phenyl and naphthyl, and examples of the substituent include styryl, cumyl, and alkyl (e.g., methyl, ethyl, etc.). The number of the substituents is, for example, 1 to 5, and when a plurality of substituents are present, they may be the same or different. Examples of the "optionally substituted aromatic group" include phenyl, naphthyl, polystyrylphenyl, cumylphenyl, and alkylphenyl.

[0090] Examples of anionic surfactants suitable for the present invention include saturated or unsaturated fatty acids, alkylbenzenesulfonic acids, dialkylsulfosuccinic acids, α-olefinsulfonic acids, alkanesulfonic acids, N-acylmethyltauric acids, alkylsulfuric acids, alkenylsulfuric acids, polyoxyalkylene alkyl ether sulfuric acids, polyoxyalkylene alkenyl ether sulfuric acids, polyoxyalkylene alkylaryl ether sulfuric acids, polyoxyalkylene alkenylaryl ether sulfuric acids, polyoxyalkylene mono- or dialkyl ether phosphoric acids, polyoxyalkylene mono- or dialkenyl ether phosphoric acids, polyoxyalkylene mono- or diphenyl ether phosphoric acids, and polyoxyalkylene alkyl ether carboxylic acids. , polyoxyalkylene alkenyl ether carboxylic acids, polyoxyalkylene alkyl ether acetic acids, polyoxyalkylene alkenyl ether acetic acids, polyoxyalkylene alkyl amide ether carboxylic acids, polyoxyalkylene alkenyl amide ether carboxylic acids, polyoxyalkylene aryl phenyl ether sulfuric acids, polyoxyalkylene aryl phenyl ether phosphoric acids, alkyl naphthalene sulfonic acids, and various salts thereof (fatty acid salts, carboxylates, sulfonates, succinates), polycarboxylates, (meth)acrylic acid-styrene copolymers, (meth)acrylic acid-(meth)acrylic acid ester copolymers, styrene-maleic acid copolymers, and phosphate esters.

[0091] In the present invention, the anionic surfactant is preferably an anionic surfactant having a carboxylic acid group, a phosphoric acid group, or a sulfonic acid group. Examples of commercially available products include "Ajisper PA111" (higher fatty acid ester) manufactured by Ajinomoto Fine-Techno Co., Ltd., and the Marialim (registered trademark) series manufactured by NOF Corporation ("Marialim AKM1511-60", "Marialim AKM0531", "Marialim AFB-1521", "Marialim A-60", "Marialim A-20", etc.).

[0092] From the viewpoint of preventing aggregation of calcium oxide and gelation of the composition varnish, the content of the (D) component is preferably 5 to 25 mass %, more preferably 7 to 23 mass %, and even more preferably 10 to 20 mass %, relative to 100 mass % of the nonvolatile content of the sealing composition.

[0093] <Other ingredients> The sealing composition of the present invention may contain components other than the components (A) to (D) (hereinafter, sometimes referred to as "other components") within the range that does not impair the effects of the present invention. Examples of other components include liquid olefin polymers, tackifiers, epoxy-modified olefin polymers having a number average molecular weight of less than 10,000, antioxidants, curing accelerators, plasticizers, etc. These may be used alone or in combination of two or more.

[0094] (Liquid olefin polymer (hereinafter also referred to as "component (E)")) Component (E) is a liquid olefin polymer excluding components (A) and (B). By adding component (E), it is possible to impart good adhesion and flexibility to the sealing layer to be formed.

[0095] In the present invention, "liquid" in "liquid olefin polymer" means that the viscosity at 25°C is 5,000 Pa s or less. In addition, in the present invention, "viscosity at 25°C" means a viscosity calculated by multiplying the dynamic viscosity at 25°C measured by a dynamic viscoelasticity measuring device by the density. An example of a dynamic viscoelasticity measuring device is a rheometer manufactured by TA Instruments (product name: DISCOVERY HR-2), etc.

[0096] In the present invention, a liquid olefin polymer having an acid anhydride group and / or a carboxy group and a number average molecular weight of less than 10,000 is classified as component (A). In addition, in the present invention, a liquid olefin polymer having a number average molecular weight of 10,000 or more is classified as component (B). Therefore, component (E) in the present invention is a liquid olefin polymer other than components (A) and (B).

[0097] From the viewpoint of good adhesion and flexibility of the formed sealing layer, the viscosity of component (E) at 25° C. is preferably 5 to 5,000 Pa·s, more preferably 10 to 4,000 Pa·s, and even more preferably 20 to 3,000 Pa·s.

[0098] From the viewpoint of good coatability of the varnish of the sealing composition, the number average molecular weight of the (E) component is preferably 100 to 50,000, more preferably 200 to 30,000, and even more preferably 300 to 20,000.

[0099] As the component (E), a commercially available product can be used. Examples of such commercially available products include ENEOS "HV-300" (liquid polybutene), ENEOS "HV-1900" (liquid polybutene), ENEOS "HV-50" (liquid polybutene), ENEOS "HV-35" (liquid polybutene), Kothari "950MW" (liquid polybutene), Kothari "2400MW" (liquid olefin polymer), INEOS "H-1900" (liquid polybutene), INEOS "H-6000" (liquid polybutene), and the like. Polybutene), INEOS "H-18000" (liquid polybutene), NOF Corporation "200N" (liquid polybutene), Nippon Soda Co., Ltd. "BI-2000" (hydrogenated polybutadiene), Nippon Soda Co., Ltd. "BI-3000" (hydrogenated polybutadiene), Nippon Soda Co., Ltd. "GI-3000" (hydrogenated polybutadiene), Mitsui Chemicals Inc. "Lucant LX100" (liquid olefin polymer), Mitsui Chemicals Inc. "Lucant LX400" (liquid olefin polymer), Idemitsu Showa Shell Co., Ltd. "Poly bd R-45HT" (liquid butadiene rubber), Idemitsu Showa Shell Co., Ltd. "Poly bd R-15HT" (liquid butadiene rubber), Idemitsu Showa Shell Co., Ltd. "Poly ip" (liquid polyisoprene), Nippon Soda's "B-1000" (liquid polybutadiene), Nippon Soda's "B-3000" (liquid polybutadiene), Nippon Soda's "G-3000" (liquid polybutadiene), Kuraray's "LIR-30" (liquid polyisoprene), Kuraray's "LIR-390" (liquid polyisoprene), Kuraray's "LIR-290" (liquid polyisoprene), Kuraray's "LBR-302" (liquid polybutadiene), Kuraray's "LBR-305" (liquid polybutadiene), Kuraray's "LBR-361" (liquid polybutadiene), Kuraray's "L-SBR-820" (liquid styrene-butadiene random copolymer), CRAY VALLEY's "Ricon154" (liquid butadiene), CRAY Examples include "RICON 184" (liquid styrene-butadiene random copolymer) manufactured by VALLEY.

[0100] Component (E) is preferably liquid polybutene and / or hydrogenated polybutadiene, and more preferably liquid polybutene.

[0101] When the component (E) is used, the content thereof is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, relative to 100% by mass of the nonvolatile content of the sealing composition, from the viewpoint of good adhesion and flexibility of the sealing layer to be formed, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. In one embodiment of the present invention, the content of the component (E) is preferably 3 to 50% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 30% by mass, relative to 100% by mass of the nonvolatile content of the sealing composition.

[0102] (Tackifier (hereinafter also referred to as "Component (F)")) The tackifier is a component that imparts adhesion to the sealing composition. Examples of the tackifier include rosin resins, terpene resins, modified terpene resins (hydrogenated terpene resins, terpene-phenol copolymer resins, aromatic modified terpene resins, etc.), petroleum resins (aliphatic petroleum resins, hydrogenated petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins), coumarone-indene resins, alkylphenol resins, xylene resins, etc.

[0103] The tackifier may be a commercially available product. Examples of the commercially available product include the following: Rosin-based resins include Pine Crystal ME-H, Pine Crystal ME-D, Pine Crystal ME-G, Pine Crystal KR-85, Pine Crystal KE-311, Pine Crystal KE-359, Pine Crystal D-6011, Pine Crystal PE-590, Pine Crystal KE-604, and Pine Crystal PR-580 (all manufactured by Arakawa Chemical Industries Co., Ltd.).

[0104] Examples of terpene resins include YS Resin PX1000, YS Resin PX1150, YS Resin PX1150N, YS Resin PX1250, YS Resin TH130, YS Resin TR105, YS Resin LP, and YS Resin CP (all manufactured by Yasuhara Chemical Co., Ltd.).

[0105] Examples of hydrogenated terpene resins include Clearon P, Clearon M, and Clearon K series (all manufactured by Yasuhara Chemical Co., Ltd.).

[0106] Examples of the terpene phenol copolymer resin include YS Polystar 2000, Polystar U, Polystar T, Polystar S, and Mighty Ace G (all manufactured by Yasuhara Chemical Co., Ltd.).

[0107] Examples of aromatic modified terpene resins include YS Resin TO85, YS Resin TO105, YS Resin TO115, and YS Resin TO125 (all manufactured by Yasuhara Chemical Co., Ltd.).

[0108] Examples of hydrogenated petroleum resins include Escorez 5300 series and 5600 series (all manufactured by Exxon Mobil Corporation); T-REZ OP501, T-REZ PR803, T-REZ HA085, T-REZ HA103, T-REZ HA105, and T-REZ HA125 (all hydrogenated dicyclopentadiene-based petroleum resins, manufactured by ENEOS Corporation); Quintone 1325 and Quintone 1345 (all manufactured by Zeon Corporation); Imave S-100, Imave S-110, Imave P-100, Imave P-125, and Imave P-140 (all hydrogenated dicyclopentadiene-based petroleum resins, manufactured by Idemitsu Kosan Co., Ltd.); Alcon P-90, Alcon P-100, Alcon P-115, Alcon P-125, Alcon P-140, Alcon M-90, and Alcon M-100, Alcon M-115, Alcon M-135, TFS13-030 (all manufactured by Arakawa Chemical Industries, Ltd.), etc.

[0109] Examples of aromatic petroleum resins include ENDEX155 (manufactured by Eastman Corporation); Neopolymer L-90, Neopolymer 120, Neopolymer 130, Neopolymer 140, Neopolymer 150, Neopolymer 170S, Neopolymer 160, Neopolymer E-100, Neopolymer E-130, Neopolymer M-1, Neopolymer S, Neopolymer S100, Neopolymer 120S, Neopolymer 130S, Neopolymer EP-140 (all manufactured by ENEOS Corporation); Petcol LX, Petcol 120, Petcol 130, Petcol 140 (all manufactured by Tosoh Corporation); T-REZ RB093, T-REZ RC100, T-REZ RC115, T-REZ RC093, T-REZ RE100 (all manufactured by ENEOS Corporation).

[0110] Examples of copolymerized petroleum resins include T-REZ HB103, T-REZ HB125, TREZ PR801, T-REZ PR802, and T-REZ RD104 (all manufactured by ENEOS Corporation); Petrotac 60, Petrotac 70, Petrotac 90, Petrotac 90HS, Petrotac 90V, and Petrotac 100V (all manufactured by Tosoh Corporation); and Quintone D100 (manufactured by Zeon Corporation).

[0111] From the viewpoint of the heat resistance of the sealing layer to be formed, the softening point of the tackifier is preferably from 50 to 200° C., more preferably from 90 to 180° C., and even more preferably from 100 to 170° C. The softening point is measured by the ring and ball method in accordance with JIS K2207.

[0112] When a tackifier is used, the content thereof is preferably 1 to 50 mass %, more preferably 2 to 40 mass %, and even more preferably 5 to 30 mass %, relative to 100 mass % of the non-volatile content of the sealing composition, from the viewpoint of the adhesion and sealing properties of the sealing layer to be formed.

[0113] (Epoxy-modified olefin polymer with a number-average molecular weight of less than 10,000) The term "epoxy-modified olefin polymer" is synonymous with "olefin polymer having an epoxy group." The epoxy-modified olefin polymer having a number average molecular weight of less than 10,000 is as described above for the component (B2) except that the number average molecular weight is less than 10,000. The epoxy groups of the epoxy-modified olefin polymer form a crosslinked structure by reacting with the acid anhydride groups / carboxy groups in the olefin polymer having an acid anhydride group and / or a carboxy group (component (B1) and, in some cases, component (A)), and can improve the dispersibility of calcium oxide (component (C)) in the sealing composition and the water vapor barrier properties of the resulting sealing layer.

[0114] (Antioxidants) In the present invention, the antioxidant is not particularly limited, and known antioxidants can be used. For example, "Irganox 1010" (hindered phenol-based antioxidant) manufactured by BASF can be used. When an antioxidant is used, the content thereof is preferably 0.01 to 5 mass%, more preferably 0.05 to 2.5 mass%, and even more preferably 0.10 to 2 mass%, based on 100 mass% of the nonvolatile content of the sealing composition.

[0115] (Cure accelerator) In the present invention, a curing accelerator may be used to accelerate the crosslinking reaction between the acid anhydride groups and / or carboxy groups of the components (B1) and (A) and the epoxy groups of the component (B2) (and optionally the epoxy-modified olefin-based polymer having a number average molecular weight of less than 10,000). Examples of the curing accelerator include imidazole compounds, tertiary and quaternary amine compounds, dimethylurea compounds, and organic phosphine compounds.

[0116] Examples of the imidazole compound include 1H-imidazole, 2-methylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 2-phenyl-4,5-bis(hydroxymethyl)imidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2-phenylimidazole, 2-dodecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Specific examples of imidazole compounds include Curezol 2MZ, 2P4MZ, 2E4MZ, 2E4MZ-CN, C11Z, C11Z-CN, C11Z-CNS, C11Z-A, 2PHZ, 1B2MZ, 1B2PZ, 2PZ, C17Z, 1.2DMZ, 2P4MHZ-PW, 2MZ-A, and 2MA-OK (all manufactured by Shikoku Chemical Industry Co., Ltd.).

[0117] The tertiary and quaternary amine compounds are not particularly limited, and examples thereof include quaternary ammonium salts such as tetramethylammonium bromide, tetrabutylammonium bromide, and triethylmethylammonium 2-ethylhexanoate; diazabicyclo compounds such as DBU (1,8-diazabicyclo[5.4.0]undecene-7), DBN (1,5-diazabicyclo[4.3.0]nonene-5), DBU-phenol salt, DBU-octylate salt, DBU-p-toluenesulfonate, DBU-formate, and DBU-phenol novolac resin salt; tertiary amines such as benzyldimethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(dimethylaminomethyl)phenol (TAP) or salts thereof; and dimethylurea compounds such as aromatic dimethylurea and aliphatic dimethylurea.

[0118] Examples of the dimethylurea compound include aromatic dimethylureas such as DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea) and U-CAT3512T (manufactured by San-Apro Co., Ltd.); and aliphatic dimethylureas such as U-CAT3503N (manufactured by San-Apro Co., Ltd.). Among these, aromatic dimethylureas are preferably used from the viewpoint of curability.

[0119] Examples of the organic phosphine compound include triphenylphosphine, tetraphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tri-tert-butylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, triphenylphosphine triphenylborane, etc. Specific examples of the organic phosphine compound include TPP, TPP-MK, TPP-K, TTBuP-K, TPP-SCN, TPP-S (all manufactured by Hokko Chemical Industry Co., Ltd.), etc.

[0120] When a curing accelerator is used, the content thereof is preferably 0.001 to 5 mass%, more preferably 0.001 to 2.5 mass%, and even more preferably 0.001 to 1 mass%, relative to 100 mass% of the nonvolatile content of the sealing composition, in order to promote the crosslinking reaction between the acid anhydride groups and / or carboxy groups of the components (B1) and (A) and the epoxy groups of the component (B2) (and optionally the epoxy-modified olefin-based polymer having a number average molecular weight of less than 10,000).

[0121] (Plasticizer) Examples of the plasticizer include mineral oils such as paraffin-based process oil, naphthene-based process oil, liquid paraffin, and Vaseline; and vegetable oils such as castor oil, cottonseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, and olive oil.

[0122] When a plasticizer is used, the content thereof is preferably 2 to 30 mass %, more preferably 4 to 25 mass %, and even more preferably 5 to 20 mass %, relative to 100 mass % of the non-volatile content of the sealing composition, from the viewpoint of the flexibility of the sealing layer to be formed.

[0123] [Method of manufacturing the sealing composition] A preferred method for producing the encapsulating composition of the present invention will be described below, although the encapsulating composition of the present invention may be produced by a method other than the method described below.

[0124] A suitable method for producing the sealing composition of the present invention (hereinafter referred to as the "production method of the present invention") includes a step of pulverizing a mixture containing an olefin polymer having an acid anhydride group and / or a carboxyl group and having a number average molecular weight of less than 10,000 (i.e., component (A)), a polymer having a number average molecular weight of 10,000 or more (i.e., component (B)), calcium oxide having a median diameter of more than 300 nm, a nonionic surfactant and / or anionic surfactant (i.e., component (D)), and an organic solvent. The sealing composition of the present invention can also be produced by mixing calcium oxide having a median diameter of 300 nm or less (i.e., component (C)) with a component other than component (C). However, such a simple mixing makes it difficult to disperse fine calcium oxide well in the sealing composition compared to the case where the above steps are taken. In addition, fine calcium oxide has a large surface area, and as a result, it also has a high hygroscopicity. In order to avoid such moisture absorption, the handleability of fine calcium oxide during the production of the sealing composition is inferior to that of calcium oxide of normal size. Therefore, the sealing composition of the present invention is preferably produced through the above steps. The mixture for the grinding treatment and the like used in the production method of the present invention will be described below in order.

[0125] A mixture for grinding can be produced by mixing calcium oxide having a median diameter of more than 300 nm, component (A), component (D) and an organic solvent. The mixture for grinding may be produced by further mixing an olefin-based polymer having an acid anhydride group and / or a carboxyl group, which is component (B1). The content of the calcium oxide is preferably 3 to 75 mass%, more preferably 5 to 70 mass%, based on the entire mixture for grinding. The content of component (A) is preferably 3 to 40 mass%, more preferably 5 to 35 mass%, based on the entire mixture for grinding. The content of component (D) is preferably 3 to 40 mass%, more preferably 5 to 35 mass%, based on the entire mixture for grinding. The content of the organic solvent is preferably 20 to 80 mass%, more preferably 30 to 70 mass%, based on the entire mixture for grinding. Components other than those described above (the above "other components") may be added to the mixture for grinding. There is no particular limitation on the order of addition of each component, and each component may be added sequentially or simultaneously.

[0126] Examples of organic solvents that can be used in the production method of the present invention include ketones such as acetone, methyl ethyl ketone, and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; cellosolves such as cellosolve; carbitols such as butyl carbitol; aromatic hydrocarbons such as toluene and xylene; amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; and the like. Commercially available organic solvents, such as "Swasol" manufactured by Maruzen Petrochemical Co., Ltd. and "Ipsol" manufactured by Idemitsu Kosan Co., Ltd., may also be used. Only one type of organic solvent may be used, or two or more types may be used in combination.

[0127] The pulverization process can be carried out using a known pulverizer. The calcium oxide is pulverized and dispersed in the mixture by the pulverization process. Examples of known pulverizers include a wet bead mill, a planetary ball mill, an attritor, a jet mill, a ball mill, and a vibration ball mill. Examples of materials for the beads include zirconia, alumina, glass, and steel. The diameter of the beads is, for example, about 0.03 to 5 mm. The rotation speed of the rotating shaft of the bead mill is, for example, about 10 to 10,000 rpm. The flow rate of the mixture for pulverization to be supplied to the pulverization chamber of the bead mill is, for example, about 0.1 to 10,000 kg / hour. In the wet pulverization using a bead mill, it is preferable to perform the pulverization process while cooling with chilled water in order to suppress the temperature rise of the mixture during the pulverization process. The temperature of the chilled water is, for example, about 0 to 40°C.

[0128] Furthermore, the mixture after the pulverization may be mixed with any component. For example, a liquid olefin polymer, a tackifier, etc. may be added and mixed with the mixture after the pulverization. When the sealing composition contains an olefin polymer having an epoxy group, which is the component (B2), it is preferable to mix the mixture after the pulverization with the component (B2) in order to prevent the crosslinking reaction from proceeding due to heat or the like during the pulverization. That is, the production method of the present invention preferably further includes a step of mixing the mixture after the pulverization with an olefin polymer having an epoxy group (i.e., the component (B2)). The olefin polymer having an acid anhydride group and / or a carboxy group, which is the component (B1), may also be mixed with the mixture after the pulverization. The component (B1) is preferably mixed with the mixture after the pulverization in order to prevent the viscosity of the mixture from increasing during the pulverization. There is no particular limitation on the order of addition of each component, and each component may be added sequentially or simultaneously.

[0129] The varnish of the sealing composition containing the organic solvent obtained as described above may have the organic solvent partly or entirely removed by drying, etc. The sealing composition of the present invention may be used in a liquid form such as a varnish, or in a solid form such as a film.

[0130] [Sealing sheet] The present invention also provides a sealing sheet having a laminated structure including a support and a sealing layer formed from the sealing composition of the present invention. A protective sheet may be used in the present invention. That is, the sealing sheet of the present invention may have a laminated structure including a support, a sealing layer, and a protective sheet in this order. Other layers may be present between the support and the sealing layer, and between the sealing layer and the protective sheet. Examples of the other layers include an adhesive layer, a release layer, and a sealing layer formed from a sealing composition that does not contain calcium oxide.

[0131] The haze of the sealing layer is preferably less than 60%, more preferably 40% or less, and even more preferably 30% or less. There is no particular limitation on the lower limit of the haze of the sealing layer, but the haze of the sealing layer is, for example, 0% or more. This haze can be measured in accordance with JIS K 7136. In detail, this haze can be measured by the method described in the Examples section below, using glass as a reference and D65 light.

[0132] Examples of the support and protective sheet include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; cycloolefin polymers; polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate; polycarbonate; and plastic films such as polyimide. The support and protective sheet may be either a single-layer film or a laminated film.

[0133] As the support and the protective sheet, for example, a low moisture permeable film having a barrier layer, or a laminated film of a low moisture permeable film having a barrier layer and another film can be used. Examples of the barrier layer include inorganic films such as silica vapor deposition films, silicon nitride films, and silicon oxide films. The barrier layer may be composed of multiple layers of multiple inorganic films (for example, silica vapor deposition films). The barrier layer may also be composed of an organic material and an inorganic material, or may be a composite multilayer of an organic layer and an inorganic film.

[0134] In the protective sheet, the surface in contact with the sealing layer is preferably release-treated. On the other hand, the support may or may not be release-treated. Examples of the release treatment include a release treatment using a release agent such as a silicone resin-based release agent, an alkyd resin-based release agent, or a fluororesin-based release agent.

[0135] The thicknesses of the support and the protective sheet are not particularly limited, but from the viewpoint of the handling property of the sealing sheet, each is preferably 10 to 150 μm, more preferably 20 to 100 μm. When the support and the protective sheet are laminated films, the thicknesses are the thicknesses of the laminated films. On the other hand, the thickness of the sealing layer is preferably 2 to 100 μm, more preferably 2 to 75 μm, and even more preferably 3 to 50 μm, from the viewpoints of transparency, sealing property, and adhesion.

[0136] [Method of manufacturing encapsulating sheet] The encapsulating sheet of the present invention can be produced, for example, by applying the varnish of the encapsulating composition obtained as described above to a support to form a coating film, and drying the resulting coating film to form a sealing layer. Also, an encapsulating sheet having a laminated structure including a support, a sealing layer, and a protective sheet in this order can be produced, for example, by applying and drying a varnish to one of the support and the protective sheet to form a sealing layer, and laminating the other of the support and the protective sheet on the formed sealing layer.

[0137] When the (B2) component is used, in order to proceed with the reaction between the epoxy groups of the (B2) component and the acid anhydride groups and / or carboxy groups of the (B1) component (and optionally the (A) component), it is preferable to dry the coating film (i.e., remove the organic solvent) by heating the coating film. The heating temperature of the coating film is preferably 50 to 200°C, more preferably 80 to 150°C, and the heating time is preferably 1 to 60 minutes, more preferably 5 to 30 minutes. The coating film may be heated under normal pressure or under reduced pressure.

[0138] The coating film obtained by removing the organic solvent may be further heated (aged). The heating temperature is preferably 80 to 200°C, more preferably 100 to 150°C, and the heating time is preferably 10 to 240 minutes, more preferably 30 to 180 minutes. The heating may be performed under normal pressure or under reduced pressure.

[0139] [Electronic Devices] The present invention also provides an electronic device comprising a sealing layer formed from the sealing composition of the present invention. Examples of the electronic device include an organic electroluminescence (EL) device, an organic light-emitting diode (OLED), a solar cell (particularly, an organic solar cell (organic thin-film solar cell (OPV), a perovskite solar cell (PSC), a dye-sensitized solar cell (DSCC))), a sensor device, a touch panel having a conductive substrate, and the like. The electronic device is preferably an electronic device that is sensitive to moisture, such as an organic electroluminescence (EL) device or a solar cell. EXAMPLES

[0140] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the above and below spirit, all of which are included in the technical scope of the present invention. Note that "parts" and "%" in the amounts of components and copolymerized units mean "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0141] <Ingredients> The components used in the examples and comparative examples are shown below. (A) Component: <Olefin polymer with acid anhydride group / carboxyl group and Mn<10,000> "HV-300M" (manufactured by Toho Chemical Industry Co., Ltd.): Maleic anhydride modified liquid polybutene, acid anhydride group concentration 0.77mmol / g, number average molecular weight 2,100

[0142] (B1) Ingredients: <Olefin polymer having acid anhydride group / carboxyl group and Mn≧10,000> "ER645" (Seiko PMC, maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer, butyl methacrylate unit concentration: 0.32 mmol / g, acid anhydride group concentration: 1.18 mmol / g, number average molecular weight: 59,000, propylene unit / butene unit: 71% / 29%) (non-volatile content: 20%) "ER661" (Seiko PMC, maleic anhydride-butyl methacrylate random copolymer modified butyl rubber, butyl methacrylate unit concentration: 0.32 mmol / g, acid anhydride group concentration: 0.46 mmol / g, number average molecular weight: 40,000, isobutene unit / isoprene unit: 98.9% / 1.1%) (non-volatile content: 35%)

[0143] (B2) Ingredients: <Olefin polymer having epoxy groups and Mn≧10,000> "ER829" (Seiko PMC, glycidyl methacrylate modified propylene-butene random copolymer, propylene unit / butene unit: 71% / 29%, epoxy group concentration: 0.64mmol / g, number average molecular weight: 168,000) (non-volatile content: 15%) "ER866" (Seiko PMC, glycidyl methacrylate modified butyl rubber, epoxy group concentration: 1.63 mmol / g, number average molecular weight: 113,000, isobutene unit / isoprene unit: 98.9% / 1.1%) (non-volatile content: 27.5%)

[0144] (B3) Ingredients: <Non-liquid olefin polymer having Mn≧10,000 and containing no acid anhydride group, no carboxy group, and no epoxy group> "BUTYL065" (JSR Corporation, butyl rubber, isobutene unit / isoprene unit: 98.7% / 1.3%)

[0145] (C) Ingredients: Calcium oxide (Yoshizawa Lime Industry Co., Ltd., median diameter: 2.1 μm)

[0146] (D) Ingredients: <Nonionic surfactant> "Disparlon DA-550" (Kusumoto Chemicals Co., Ltd.): Nonionic surfactant "Paionin D-7240" (Takemoto Oil Co., Ltd.): Polyoxyethylene naphthyl ether "Paionin D-1004" (Takemoto Oil Co., Ltd.): Polyoxyethylene octyl ether <Anionic surfactants> "Ajisper PA111" (Ajinomoto Fine-Techno Co., Ltd.): Acidic dispersant (acid value 35 mg KOH / g)

[0147] (E) Ingredients: <Liquid olefin polymer> "HV-1900" (ENEOS Corporation, liquid polybutene, number average molecular weight: 2,900, viscosity at 25°C: 460 Pa s)

[0148] (F) Ingredients: <Tackifier> "Alcon P-125" (Arakawa Chemical Industries, hydrogenated petroleum resin, softening point: 125°C)

[0149] Other Ingredients: <Antioxidants> "Irganox 1010" (BASF): Hindered phenol antioxidant <Curing accelerator> 2,4,6-Tris(dimethylaminomethyl)phenol (manufactured by Nouryon Chemical Industries, hereafter abbreviated as "TAP") <Moisture-absorbing filler> Semi-calcined hydrotalcite (Kyowa Chemical Industry Co., Ltd. "DHT-4C", median diameter: 400 nm, BET specific surface area: 15 m 2 / g) <Cationic surfactant> "Ajisper PB821" (manufactured by Ajinomoto Fine-Techno Co., Ltd.): Basic dispersant (amine value 10 mg KOH / g, acid value 17 mg KOH / g)

[0150] <Example 1> A varnish having the compounding ratio shown in the table below was prepared by the following procedure, and a sealing sheet was prepared using the obtained varnish. The amount (parts) of each component shown in the table below indicates the amount of non-volatile content of each component in the varnish. In the table below, calcium oxide is described as "CaO" and its median diameter is described in parentheses.

[0151] Specifically, maleic anhydride-modified liquid polybutene ("HV-300M" manufactured by Toho Chemical Industry Co., Ltd.), calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd.), nonionic surfactant ("Disparlon DA-550" manufactured by Kusumoto Chemical Industry Co., Ltd.), and toluene were blended to obtain a mixture for grinding treatment (toluene content: 56.5%, maleic anhydride-modified liquid polybutene content: 9%, calcium oxide content: 30%, nonionic surfactant content: 4.5% relative to the total mixture).

[0152] The mixture for grinding was placed in a wet bead mill (Ashizawa Finetech's "Labostar Mini LMZ015"), and beads (bead diameter: 0.1 mm) were filled in so that the volume was approximately 60% of the effective volume of the grinding chamber. The mixture was then ground to obtain a post-grinding mixture in which calcium oxide was ground and dispersed.

[0153] A small amount was taken from the mixture after the grinding process and diluted 100 times with toluene to prepare a measurement sample, and the median diameter of calcium oxide was measured and calculated by dynamic light scattering using a nanoparticle size measurement device "NANOTRAC WAVE" manufactured by Microtrac Co., Ltd. As a result, the median diameter of calcium oxide was 200 nm.

[0154] The mixture after the grinding treatment was mixed with a swasol solution (non-volatile content: 60%) of a tackifier ("Arcon P-125" manufactured by Arakawa Chemical Industries Co., Ltd.), liquid polybutene ("HV-1900" manufactured by ENEOS Corporation), a glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation), a maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Corporation), a hindered phenol-based antioxidant ("Irganox 1010" manufactured by BASF Corporation), and a curing accelerator (TAP, manufactured by Nouryon Chemical Industries Co., Ltd.), and the resulting mixture was mixed in a high-speed rotating mixer to obtain a varnish of a sealing composition.

[0155] A polyethylene terephthalate film with one side treated with a silicone-based release agent ("SP3000" manufactured by Toyo Cross Co., Ltd., PET film thickness: 50 μm) and a low moisture permeable polyethylene terephthalate film ("Techbarrier HX" manufactured by Mitsubishi Chemical Corporation, PET film thickness: 12 μm) were laminated together so that the side of SP3000 not treated with the silicone-based release agent was in contact with Techbarrier HX to produce a laminated film, which was used as a support and protective sheet for the sealing sheet. Hereinafter, the "side of the laminated film treated with the silicone-based release agent" will be referred to as the "release-treated side".

[0156] The obtained varnish was uniformly applied onto the release-treated surface of the laminated film by a die coater, and heated at 150° C. for 10 minutes to obtain a sealing sheet having a sealing layer with a thickness of 10 μm.

[0157] <Example 2> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that the amount of a toluene solution of a glycidyl methacrylate-modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation) was changed from 10 parts to 0 parts.

[0158] <Example 3> A sealing composition varnish and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that the amount of a toluene solution of a maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Corporation) was changed from 10 parts to 0 parts.

[0159] <Example 4> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) was changed to "Paionin D-7240" (manufactured by Takemoto Oil & Fat Co., Ltd.).

[0160] <Example 5> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) was changed to "Paionin D-1004" (manufactured by Takemoto Oil & Fat Co., Ltd.).

[0161] <Example 6> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) was changed to "Ajisper PA111" (manufactured by Ajinomoto Fine-Techno Co., Ltd.).

[0162] <Example 7> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that the amount of "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) used was changed from 45 parts to 90 parts.

[0163] <Example 8> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that the amount of "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) used was changed from 45 parts to 20 parts.

[0164] <Example 9> A sealing sheet having a varnish of the sealing composition and a sealing layer having a thickness of 10 μm was prepared in the same manner as in Example 1, except that the glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC) was changed to glycidyl methacrylate modified butyl rubber ("ER866" manufactured by Seiko PMC), and the maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC) was changed to maleic anhydride-butyl methacrylate random copolymer modified butyl rubber ("ER661" manufactured by Seiko PMC).

[0165] <Example 10> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were produced in the same manner as in Example 1, except that the amount of calcium oxide used was changed from 300 parts to 150 parts.

[0166] <Example 11> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were produced in the same manner as in Example 1, except that the amount of calcium oxide used was changed from 300 parts to 45 parts.

[0167] <Example 12> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that the toluene solution of glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation) and the maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Corporation) were changed to glycidyl methacrylate modified butyl rubber ("ER866" manufactured by Seiko PMC Corporation).

[0168] <Example 13> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that the glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation) and the maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Corporation) were changed to butyl rubber ("BUTYL065" manufactured by JSR Corporation).

[0169] <Example 14> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that the amount of a toluene solution of a glycidyl methacrylate-modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation) was changed from 10 parts to 20 parts.

[0170] <Example 15> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that a swasol solution (non-volatile content: 60%) of a tackifier ("Alcon P-125" manufactured by Arakawa Chemical Industries, Ltd.) was not mixed into the mixture after the grinding treatment.

[0171] <Comparative Example 1> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Corporation) and maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Corporation) were not added to the mixture after the grinding treatment.

[0172] <Comparative Example 2> A varnish of a sealing composition and a sealing sheet having a sealing layer having a thickness of 10 μm were prepared in the same manner as in Example 1, except that maleic anhydride-modified liquid polybutene ("HV-300M" manufactured by Toho Chemical Industry Co., Ltd.) was not mixed into the mixture for grinding treatment.

[0173] <Comparative Example 3> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) was not added to the mixture for grinding treatment.

[0174] <Comparative Example 4> A swasol solution (non-volatile content: 60%) of a tackifier ("Arcon P-125" manufactured by Arakawa Chemical Industries Co., Ltd.) was mixed with maleic anhydride modified liquid polybutene ("HV-300M" manufactured by Toho Chemical Industry Co., Ltd.), liquid polybutene ("HV-1900" manufactured by ENEOS Corporation), semi-calcined hydrotalcite ("DHT-4C" manufactured by Kyowa Chemical Industry Co., Ltd.), and "Disparlon DA-550" (manufactured by Kusumoto Chemical Co., Ltd.) using a three-roll mill to obtain a mixture. The obtained mixture was mixed with glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC), maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC), hindered phenol-based antioxidant ("Irganox 1010" manufactured by BASF), curing accelerator (TAP, manufactured by Kayaku Nouryon) and toluene, and mixed with a high-speed rotating mixer to obtain a varnish of a sealing composition. A sealing sheet having a sealing layer with a thickness of 10 μm was produced from the obtained varnish by the same method as in Example 1.

[0175] <Comparative Example 5> A swasol solution (non-volatile content: 60%) of a tackifier ("Arcon P-125" manufactured by Arakawa Chemical Industries Co., Ltd.) was mixed with maleic anhydride modified liquid polybutene ("HV-300M" manufactured by Toho Chemical Industries Co., Ltd.), liquid polybutene ("HV-1900" manufactured by ENEOS Corporation), "Disparlon DA-550" (manufactured by Kusumoto Chemical Industries Co., Ltd.), glycidyl methacrylate modified propylene-butene random copolymer ("ER829" manufactured by Seiko PMC Co., Ltd.), maleic anhydride-butyl methacrylate random copolymer modified propylene-butene random copolymer ("ER645" manufactured by Seiko PMC Co., Ltd.), hindered phenol-based antioxidant ("Irganox 1010" manufactured by BASF), curing accelerator (TAP, manufactured by Kayaku Nouryon Co., Ltd.) and toluene, and mixed in a high-speed rotating mixer to obtain a varnish of a sealing composition. From the obtained varnish, in the same manner as in Example 1, an encapsulating sheet having an encapsulating layer with a thickness of 10 μm was produced.

[0176] <Comparative Example 6> A varnish of a sealing composition and a sealing sheet having a sealing layer with a thickness of 10 μm were prepared in the same manner as in Example 1, except that "Disparlon DA-550" (manufactured by Kusumoto Chemicals Co., Ltd.) was changed to "Ajisper PB821" (manufactured by Ajinomoto Fine-Techno Co., Ltd.).

[0177] The life of the varnishes of the sealing compositions obtained in the Examples and Comparative Examples was evaluated by the following method. In addition, the optical properties (transparency) and water vapor barrier properties of the sealing layers of the sealing sheets obtained in the Examples and Comparative Examples were evaluated by the following methods.

[0178] <Method for evaluating the varnish life of sealing composition> The varnishes of the sealing compositions prepared in the Examples and Comparative Examples were stored in a refrigerator and checked over time, and were evaluated according to the following criteria. The results are shown in the table below. 〇: Film formation is possible even after 24 hours or more from the time of varnish preparation ×: The condition deteriorates due to gelation or precipitation within 24 hours after the varnish is made, making it difficult to form a film.

[0179] <Method of evaluating optical properties (transparency)> The sealing sheets prepared in the examples and comparative examples were cut to a length of 70 mm and a width of 25 mm, the protective sheet was peeled off from the cut sealing sheet, and the sealing sheet having a laminated structure of the sealing layer / support was laminated on a glass plate ("White Slide Glass S1112 Polished Edge No. 2" manufactured by Matsunami Glass Industrial Co., Ltd., length: 76 mm, width: 26 mm, and thickness: 1.2 mm) using a batch-type vacuum laminator (manufactured by Nichigo-Morton Co., Ltd., V-160) to obtain an evaluation sample having a laminated structure of glass / sealing layer / support. The lamination conditions were a temperature of 80°C, a decompression time of 30 seconds, and then a pressure of 0.3 MPa for 30 seconds.

[0180] The haze (%) was measured according to JIS K 7136. In detail, after peeling off the support of the evaluation sample having a laminated structure of glass / sealing layer / support, the haze (%) of the evaluation sample from which the support was peeled off was measured using a haze meter HZ-V3 (halogen lamp) manufactured by Suga Test Instruments Co., Ltd., under D65 light with glass as a reference, and the transparency was evaluated according to the following criteria. The results are shown in the table below. (Transparency Standards) ○(Good): Haze is less than 30% △(Acceptable): Haze is 30% or more and less than 60% × (Poor): Haze is 60% or more

[0181] <Method for evaluating water vapor barrier properties> As a support, a composite film having an aluminum foil and a polyethylene terephthalate film ("PET-Tuki AL1N30" manufactured by Tokai Toyo Aluminium Sales Co., Ltd. (aluminum foil thickness: 30 μm, PET film thickness: 25 μm) was prepared.

[0182] Except for using the composite film as the support, a test sheet having a laminated structure of "support (composite film) / sealing layer / protective sheet (laminate film)" was obtained in the same manner as in the Examples and Comparative Examples.

[0183] A 50 mm×50 mm square glass plate made of non-alkali glass was prepared. This glass plate was washed with boiled isopropyl alcohol for 5 minutes and dried at 150° C. for 30 minutes or more.

[0184] Calcium was vapor-deposited on one side of the dried glass plate using a mask that covered the peripheral area 0 mm to 2 mm away from the edge of the glass plate, forming a calcium film (purity 99.8%) having a thickness of 200 nm on the central part of one side of the glass plate except for the peripheral area 0 mm to 2 mm away from the edge of the glass plate.

[0185] In a nitrogen atmosphere, the sealing layer of the above-mentioned test sheet and the calcium film side of the glass plate were laminated using a thermal laminator (Fujipla Co., Ltd.'s "Lamipacker DAiSY A4 (LPD2325)") to obtain a laminate. This laminate was used as an evaluation sample.

[0186] Generally, when calcium comes into contact with water and becomes calcium oxide, it becomes transparent. In the above-mentioned evaluation sample, the glass plate and aluminum foil have sufficiently high water vapor intrusion barrier properties, so that moisture usually moves in the in-plane direction (direction perpendicular to the thickness direction) through the edge of the sealing layer to reach the calcium film. When moisture infiltrates into the evaluation sample, the calcium film is gradually oxidized from the edge and becomes transparent, so that the calcium film is observed to shrink. Therefore, the moisture infiltration into the evaluation sample can be evaluated by measuring the sealing distance (mm) from the edge of the evaluation sample to the calcium film. Therefore, the evaluation sample containing the calcium film can be used as a model for an electronic device.

[0187] First, the sealing distance X2 (mm) from the end of the evaluation sample to the end of the calcium film was measured using a microscope (Mitutoyo Corporation "Measuring Microscope MF-U").

[0188] Next, the evaluation sample was placed in a thermo-hygrostat chamber set at a temperature of 85°C and a humidity of 85% RH. When the sealing distance X1 (mm) between the end of the evaluation sample placed in the thermo-hygrostat chamber and the end of the calcium film increased by 0.1 mm from the initial sealing distance X2, the evaluation sample was removed from the thermo-hygrostat chamber. The time from when the evaluation sample was placed in the thermo-hygrostat chamber to when it was removed from the thermo-hygrostat chamber was calculated as the decrease start time t [hours]. This decrease start time t was calculated as the time T when the evaluation sample was placed in the thermo-hygrostat chamber. P1 From the time T, the sealing distance X1 [mm] between the end of the evaluation sample stored in the temperature and humidity chamber and the end of the calcium film becomes "X2 + 0.1 mm". P2 corresponds to the time until

[0189] The sealing distance X1 and decrease start time t were substituted into the Fick's diffusion equation of formula (1) to calculate the constant K as a water vapor penetration barrier property parameter.

[0190]

number

[0191] Using the obtained constant K, the water vapor barrier property of the sealing layer was evaluated according to the following criteria. The smaller the value of the constant K, the higher the water vapor barrier property. In the following, "hr" means "hours." The results are shown in the table below. In the table, "(cm / hr^0.5)" means "(cm / hr 0.5 )". (Water vapor barrier standard) 〇(Good): Constant K is 0.025cm / h 0.5 less than × (defective): Constant K is 0.025 cm / hr 0.5 End

[0192] [Table 1-1]

[0193] [Table 1-2]

[0194] The results in Table 1 show that the sealing compositions of the examples of the present invention have a good evaluation of varnish life, and therefore have excellent dispersibility of calcium oxide (storage stability), and can form a sealing layer that has excellent water vapor barrier properties and optical properties (transparency). [Industrial Applicability]

[0195] The sealing composition of the present invention can form a sealing layer that has both water vapor barrier properties and transparency, and further has excellent dispersibility of calcium oxide (storage stability). Therefore, the sealing composition is useful as a sealing material for, for example, electronic devices (e.g., organic EL devices, organic light-emitting diodes (OLEDs), solar cells (particularly, organic solar cells (organic thin-film solar cells (OPV), perovskite solar cells (PSC), dye-sensitized solar cells (DSCC))), sensor devices, touch panels having conductive substrates, etc.).

Claims

1. A sealing composition comprising the following components (A) to (D): (A) an olefin polymer having an acid anhydride group and / or a carboxy group and having a number average molecular weight of less than 10,000; (B) a polymer having a number average molecular weight of 10,000 or more; (C) calcium oxide having a median diameter of 300 nm or less; and (D) a nonionic surfactant and / or an anionic surfactant, Here, the polymer (B) having a number average molecular weight of 10,000 or more is at least one selected from an olefin polymer having an acid anhydride group and / or a carboxy group and having a number average molecular weight of 10,000 or more, and an olefin polymer having an epoxy group and having a number average molecular weight of 10,000 or more.

2. 2. The sealing composition of claim 1, wherein component (D) is a nonionic surfactant.

3. 3. The sealing composition of claim 2, wherein the non-ionic surfactant is a polyoxyalkylene alkyl ether or a polyoxyalkylene aryl ether.

4. 3. The sealing composition of claim 2, wherein the non-ionic surfactant is a polyoxyalkylene aryl ether.

5. The nonionic surfactant has the following structure: 【Chemistry 1】 (wherein n is an integer from 1 to 10; R 1 and R 2 wherein each independently represents a hydrogen atom or a methyl group, and Ar represents an aromatic group which may have a substituent.

6. The sealing composition according to any one of claims 1 to 5, further comprising (E) a liquid olefin polymer (excluding the components (A) and (B)).

7. The sealing composition according to any one of claims 1 to 6, further comprising (F) a tackifier.

8. The sealing composition according to any one of claims 1 to 7, wherein the content of the component (C) is 10 to 70 mass% based on 100 mass% of the nonvolatile content of the sealing composition.

9. The sealing composition according to any one of claims 1 to 8, wherein the content of the component (D) is 5 to 25 mass% based on 100 mass% of the nonvolatile content of the sealing composition.

10. A sealing sheet having a laminated structure comprising a sealing layer formed from the sealing composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Epoxy resin molding material for sealing and electronic part device

    JP2004175842A

  • Calcium oxide dispersion liquid and its manufacturing method

    JP2006124264A

  • Dispersion of metal oxide fine particle and its manufacturing method

    JP2007197296A

  • Carrier for electrostatic charge development, developer for electrostatic charge development, developer cartridge, process cartridge, and image forming apparatus

    JP2010107588A

  • Resin composition

    JP2017122136A